Ameliorative Effects of Syzygium cumini and Morus alba Fruit Extract on the Testicular Histopathology of Lead Exposed Mice: Histopathology of Lead Exposed Mice (Biological Sciences - PJSIR, 2023)
The present study focused the toxicity of lead (Pb) on the male mice reproductive system. The research was designed to check the histopathology of male albino mice testes after lead (Pb) exposure in drinking water and the rescuing effect of post treatment with Jambul Fruit Pulp Extract (JFE) and white Mulberry Fruit Pulp Extract (MFE). There were four groups and each group having 10 animals. Control group (no treatment), Pb group (50 ppm Pb ions in drinking water for 15 days) and for the next 5 days lead free water. Pb+J group (Pb treatment as in Pb group + 0.2 mL Jambul fruit pulp extract with 12 h intervals for 16-20 days of the study. Similarly, Pb+M group (Pb treatment as in Pb group + 0.2 mL Morus fruit pulp extract with 12h intervals for 16-20 days of the study. Results revealed various characteristic changes in testicular histology. The results indicated significant alternations in organ weight, number of spermatogonia, number of spermatocytes, cross sectional area (CSA) of seminiferous tubules, seminiferous epithelial height and the number of seminiferous tubules in Pb group than the control group. These results were significantly recovered in the Pb+J and Pb+M groups.